2019
DOI: 10.1071/hc19016
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of New Zealand patients and GPs at the beginning of patient portal implementation

Abstract: INTRODUCTION: New Zealand health policy encourages patient access to their electronic medical records via portals.AIM: To discover patient and general practitioner (GP) perspectives of access to electronic medical records and e-messaging in the early portal implementation phase. METHODS:In 2014, Auckland primary health organisations and an Accident & Medical organisation were asked to invite their GPs to complete an online survey and consent for a researcher to attend their waiting room and invite patients to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The health record function provides patients options to view clinical documents that can be retrieved from health providers’ EHR [ 22 , 23 , 34 ]. This information can include problem lists [ 22 , 24 - 29 , 45 , 56 , 67 - 71 ], allergies [ 22 , 25 - 28 , 30 - 33 , 35 - 39 , 56 , 67 - 70 ], immunization [ 22 , 26 - 28 , 30 , 32 - 35 , 40 - 42 , 56 , 68 - 71 ], laboratory and test results [ 22 , 24 , 26 - 30 , 33 , 36 , 37 , 40 , 42 - 61 , 67 - 71 ], diagnostic information [ 32 , 37 , 44 , 45 , 62 ], discharge information [ 31 , 34 , 63 ], and clinical notes [ 24 , 30 , 33 , 42 , 50 , 61 , 64 , 67 , 69 ]. Figure 3 shows an example of test results in PittPHR [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The health record function provides patients options to view clinical documents that can be retrieved from health providers’ EHR [ 22 , 23 , 34 ]. This information can include problem lists [ 22 , 24 - 29 , 45 , 56 , 67 - 71 ], allergies [ 22 , 25 - 28 , 30 - 33 , 35 - 39 , 56 , 67 - 70 ], immunization [ 22 , 26 - 28 , 30 , 32 - 35 , 40 - 42 , 56 , 68 - 71 ], laboratory and test results [ 22 , 24 , 26 - 30 , 33 , 36 , 37 , 40 , 42 - 61 , 67 - 71 ], diagnostic information [ 32 , 37 , 44 , 45 , 62 ], discharge information [ 31 , 34 , 63 ], and clinical notes [ 24 , 30 , 33 , 42 , 50 , 61 , 64 , 67 , 69 ]. Figure 3 shows an example of test results in PittPHR [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The health record function provides patients options to view clinical documents that can be retrieved from health providers' EHR [22,23,34]. This information can include problem lists [22,[24][25][26][27][28][29]45,56,[67][68][69][70][71], allergies [22,25-28,30-33,35-39, 56,67-70], immunization [22,26-28,30,32-35, 40-42,56,68-71], laboratory and test results [22,24,[26][27][28][29][30]33,36,37,40,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]…”
Section: Health Recordmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Among the research papers in this issue are a paper comparing GPs' and patients' perceptions of patient portals (before they were widely implemented) 6 and another asking patients if they had received the information they would like about the medicines they were being dispensed. 7 Both papers found that patients would like more information than they currently receive but GPs were less enthusiastic than patients about their having full access to all their clinical records, 6 and no one was sure about where the responsibility should lie for providing the information about their medicines that patients would like. 7 Patients are unlikely to complain about these things, but the general message seems to be that one should not under-estimate patients' appetite for health information from their trusted sources in primary care.…”
mentioning
confidence: 99%